2012 IMJ Reviewers (Internal Medicine Journal, 2013)
Indigenous peoples remain under-represented in genomic research and clinical trials. This reflects historical exclusion, mistrust and health system barriers. In this article, we describe a single Australian institution's experience in improving engagement and enrolment of Aboriginal and Torres Strait Islander patients in a cancer genomic sequencing study. We reflect on challenges related to rapport, consent and enrolment and outline practical strategies including relationship-building, targeted resources and a tailored enrolment pathway. We contend that equitable participation in genomic research requires sustained, trust-based and culturally specific engagement, rather than reliance on purely technical or procedural solutions.